Blockchain-Inspired Lightweight Dynamic Encryption Schemes for a Secure Health Care Information Exchange System - Aruna, Etikala; Sahayadhas , Arun (Engineering, Technology & Applied Science Research, 2024)
The telemedicine sector has entered a new phase marked by the integration of Internet of Things (IoT) devices to identify and then send patient health data to medical terminals for additional diagnostic and therapeutic procedures. Today, patients can receive prompt and expert medical care at home in comfortable settings. Due to the unique nature of these services, it is essential to verify patient healthcare data, as it contains a greater amount of personal information that is vulnerable to privacy violations and data breaches. Blockchain technology has attracted interest in addressing security concerns due to its decentralized, immutable, shared, and distributed characteristics. This study proposes lightweight dynamic blockchain-enabled encryption schemes to secure physiological data during authentication and exchange processes. The proposed scheme introduces the logistic Advanced Encryption Scheme (AES) that combines chaotic logistic maps to secure the data in the blockchain network and mitigate different attacks. The model was deployed on the Ethereum blockchain and performance metrics, such as computation and transaction time, were calculated and compared with other current blockchain-inspired encryption models. Furthermore, the NIST test was conducted to prove the strength of the proposed scheme. The proposed model exhibits high security and a shorter transaction time (0.964 s) than other existing schemes. Finally, the proposed model generates high-dynamic keys that are suitable for defending against unpredictable attacks on blockchain.